ANALISIS KEANDALAN SISTEM DUMP DOOR MESIN BAGGING PHONSKA 5 MENGGUNAKAN PENDEKATAN RELIABILITY CENTERED MAINTENANCE - Abdul Aziz Rizal; Doni Yusri (Universitas Putera Batam, 2026)
The reliability of the Phonska 5 bagging machine is a crucial factor in ensuring smooth fertilizer packaging and minimizing production disruptions. The dump door system was identified as the largest contributor to failures (33%) in this unit. This study aims to analyze the reliability of the dump door system and determine appropriate maintenance strategies using the Reliability Centered Maintenance (RCM) approach. The analysis methods included system function identification, Failure Mode and Effect Analysis (FMEA), and evaluation of Mean Time Between Failure (MTBF) and Mean Time To Repair (MTTR) parameters. FMEA results showed that the sliding gate component had the highest Risk Priority Number (RPN) of 175, followed by the solenoid valve (120) and pneumatic piston (105). Reliability analysis indicated that the sliding gate had the highest MTBF of 6,243.71 hours, while the load cell had the shortest failure interval with an MTBF of 328.62 hours. The longest repair time was found in the solenoid valve with an MTTR of 20.93 hours, potentially causing significant downtime. The recommended maintenance strategy is Condition Directed Maintenance, implemented through an RCM Decision Worksheet, preventive maintenance checksheets, and One Point Lesson (OPL) to improve operational reliability